Pengaruh Rasio Keuangan Terhadap Harga Saham Dengan Per Sebagai Pemoderasi Perusahaan Sektor Kesehatan - Danang Kuncara Jakti; Rifandi, Muhamad (LPPM POLITEKNIK LP3I BANDUNG, 2024)
The study aims at finding out the effect of Current Ratio (CR), Return on Equity (ROE), and Earning per Share (EPS) on stock prices with Price Earning Ratio (PER) as the moderating variable in health sector companies listed on the Indonesia Stock Exchange in 2015-2021. The sampling in this study was purposive sampling resulting in 8 companies on the Indonesia Stock Exchange. The research is a qualitative study. The research method used multiple linear regression and residual test. The analysis tool was the SPSS version 25 program. The results of the study showed that the Current Ratio (CR) and Return on Equity (ROE) variables do not affect the stock prices of health sector companies listed on the Indonesia Stock Exchange, while the Earning per Share (EPS) variable has a positive and significant effect on stock prices of health sector companies listed on Indonesia Stock Exchange. In addition, the Price Earning Ration (PER) variable is unable to moderate the relationship between the Current Ratio (CR), Return on Equity (ROE), and Earning per Share (EPS) on stock prices of health sector companies listed on the Indonesia Stock Exchange.